Pembentukan Keluarga Sakinah Pada Keluarga Jama’ah Tablig Di Kota Palangka Raya - Rahmad Rahmad (Jurnal Studi Agama dan Masyarakat, 2015)
In this study,  used descriptive  avalitative  research with the subjeck using purposive sampling. That to be a respondent is a people’s. A people of muslim religious teacher, and 3 people’s from society that is community such a religious meeting. The objeck is a formation of harmonious  family in the community such a religious in Palangkaraya Raya city. The data collection, it used some techniques  such as interview,  and documentation  . for the data validity using triangulasi and analyzing the technique are as follows : data colection, data reduction, data display and conclusion. The  main  research  finding  were:  1)  the  method  to  making  the harmonious family must be loving, to know and function in a family, know basic right and obligation in family. In a family must to ask and more than read a book about marriage, always to communication, to believe and understanding disvantages and advantages in family and always discussion. If a aplly can their be harmonious family. 2) All of agrrement their is no the problem to  making  the harmonious  family.  3)  The  method  to  making  the harmonious family is a ablution, reading Alquran or reading a Yasin, trust in.